2020
DOI: 10.3390/molecules25081970
|View full text |Cite
|
Sign up to set email alerts
|

Concise Synthesis of Catechin Metabolites 5-(3′,4′-Dihydroxyphenyl)-γ-valerolactones (DHPV) in Optically Pure Form and Their Stereochemical Effects on Skin Wrinkle-Reducing Activities

Abstract: A concise and scalable synthetic route for optically pure (4S) and (4R)-5-(3 ,4dihydroxyphenyl)-γ-valerolactones (DHPVs), catechin metabolites, has been developed via the efficient construction of a γ-valerolactone moiety from hexenol. Noticeably, the different skin wrinkle-reducing activities of each metabolite were revealed via our unique syntheses of DHPVs in an enantiomerically pure form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
(35 reference statements)
1
5
0
Order By: Relevance
“…These results indicated that (S)-DHPV can protect against LPS-induced inflammation by inhibiting NF-κB activation through repression of IκBα degradation. The enantiomeric purities of asymmetric dihydroxylation products, 2a and 2b, and final (S)-and (R)-DHPV, 1a and 1b, were confirmed by the analytical chiral HPLC experiment (Supplementary Materials), according to previous report of Suh group [23]. The synthetic final enantiomers were pure enough for further biological study, with the enantioselectivity of 97.3:2.7 for 1a and 95.1:4.9 for 1b.…”
Section: Anti-inflammatory Activity Of (R)-and (S)-dhpv On Iec-6 Cellssupporting
confidence: 58%
See 1 more Smart Citation
“…These results indicated that (S)-DHPV can protect against LPS-induced inflammation by inhibiting NF-κB activation through repression of IκBα degradation. The enantiomeric purities of asymmetric dihydroxylation products, 2a and 2b, and final (S)-and (R)-DHPV, 1a and 1b, were confirmed by the analytical chiral HPLC experiment (Supplementary Materials), according to previous report of Suh group [23]. The synthetic final enantiomers were pure enough for further biological study, with the enantioselectivity of 97.3:2.7 for 1a and 95.1:4.9 for 1b.…”
Section: Anti-inflammatory Activity Of (R)-and (S)-dhpv On Iec-6 Cellssupporting
confidence: 58%
“…25, x FOR PEER REVIEW 4 of 9Materials), according to previous report of Suh group[23]. The synthetic final enantiomers were pure enough for further biological study, with the enantioselectivity of 97.3:2.7 for 1a and 95.1:4.9 for 1b Divergent and enantioselective synthesis of DHPV.…”
mentioning
confidence: 97%
“…These results imply that they might make good lead compounds for anti-inflammatory medications. 50 Two enantiomers of DHPV, a flavanol synthesized in the gastrointestinal tract by intestinal microbes' metabolic processes and present in nutritional plants, particularly green tea, red wine, and cocoa extracts, [118] were studied for their antiinflammatory properties on IEC-6 cells. The metabolite formed in the gut has positive effects on the IEC-6 cells of the rat intestine, as evidenced by the researchers' finding that (S)-DHPV was more active than (R)-DHPV.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…3 S ‐Flavanols yield 4 S‐ C 6 –C 5 metabolites and 3 R ‐flavanols yield 4 R ‐C 6 –C 5 metabolites. [ 90 ]…”
Section: Reporting Of Enantiomers and Diastereo‐isomersmentioning
confidence: 99%